Single-domain Antibody Inhibitors of Clostridium difficile Toxins - Hussack, Greg (Université d'Ottawa / University of Ottawa, 2011)
Clostridium difficile is a leading cause of nosocomial infection in North America and a considerable challenge to healthcare professionals in hospitals and nursing homes. The Gram-positive bacterium produces two exotoxins, toxin A (TcdA) and toxin B (TcdB), which are the major virulence factors responsible for C. difficile-associated disease (CDAD) and are targets for CDAD therapy. In this work, recombinant single-domain antibody fragments (VHHs) which target the cell receptor binding domains of TcdA or TcdB were isolated from an immune, llama phage display library and characterized. Four VHHs (A4.2, A5.1, A20.1, and A26.8) were potent neutralizers of the cytopathic effects of TcdA in an in vitro assay and the neutralizing potency was enhanced when VHHs were administered in combinations. Epitope mapping experiments revealed that some synergistic combinations consisted of VHHs recognizing overlapping epitopes, an indication that factors other than mere epitope blocking are responsible for the increased neutralization. Binding assays revealed TcdA-specific VHHs neutralized TcdA by binding to sites other than the carbohydrate binding pocket of the toxin. The TcdB-specific VHHs failed to neutralize TcdB, as did a panel of human VL antibodies isolated from a synthetic library. To enhance the stability of the C. difficile TcdA-specific VHHs for oral therapeutic applications, the VHHs were expressed with an additional disulfide bond by introducing Ala/Gly54Cys and Ile78Cys mutations. The mutant VHHs were found to be well expressed, were non-aggregating monomers, retained low nM affinity for TcdA, and were capable of in vitro TcdA neutralization. Digestion of the VHHs with the major gastrointestinal proteases, at biologically relevant concentrations, revealed a significant increase in pepsin resistance for all mutants and an increase in chymotrypsin resistance for the majority of mutants without compromising inherent VHH trypsin resistance. Collectively, the second disulfide not only increased VHH thermal stability at neutral pH, as previously shown, but also represents a generic strategy to increase VHH stability at low pH and impart protease resistance. These are all desirable characteristics for the design of protein-based oral therapeutics. In conclusion, llama VHHs represent a class of novel, non-antibiotic inhibitors of infectious disease virulence factors such as C. difficile toxins.
Keywords: Clostridium difficile; Toxin; Neutralization; Antibody; Single-domain antibody; Oral therapeutics